Entrepreneurship education: does it helps university graduates to be entrepreneurs / Noor Asiah Md Mutapa and Nurul Ezanee Ahmad Tajuddin - Md Mutapa, Noor Asiah; Ahmad Tajuddin, Nurul Ezanee (2010)
Entrepreneurship is a knowledge discipline that can be taught and should be learnt by students nowadays. The skills of entrepreneurship are an advantage to graduates in developing their own career if they fail in searching a job. In economies transition, entrepreneurship education has become an integral part of the new curriculum in universities. Entrepreneurship education is also promoted as an effective way to facilitate the transition of a growing graduate population from education into work environment. This paper is concerned on whether entrepreneurship education is helping graduates to be entrepreneur. Although many universities have provide entrepreneurship education for their students, but the rate of unemployment rate among graduates is still higher. In addition to explore on how far entrepreneurship education helps in developing career of graduates, the research sought to examine whether the skills of entrepreneurship, the content of entrepreneurship education, and the experiences given through entrepreneurship education are adequate enough in influencing graduates to be entrepreneur.